2011
DOI: 10.1007/s10460-011-9321-2
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the social bases of home gardening

Abstract: The study of alternatives to conventional industrial agricultural production has intensified in recent years. While many types of alternative production systems, and the motivations of individuals to participate in them, have been studied, there are significant gaps in the literature. One such dearth is research on those participating in self-provisioning activities. This study begins to fill the gap by looking at the self-provisioning activity of home gardening using data from the 2008 Ohio Survey of Food, Ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
84
2
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(95 citation statements)
references
References 22 publications
(29 reference statements)
6
84
2
3
Order By: Relevance
“…In this study, participants reported growing cultural or ethnic foods such as bok choy, gogi berries, chayote and green tomatoes. Similar to other research projects, many families in this study grew foods that had meaning in terms of their identity as individuals and their personal and community history (Fruge et al 2014;Schupp and Sharp 2012). The agrobiodiversity of the garden contributes to nutrition and food security by increasing the intake of culturally unique vegetables.…”
Section: Increasing Vegetable Consumptionmentioning
confidence: 87%
See 1 more Smart Citation
“…In this study, participants reported growing cultural or ethnic foods such as bok choy, gogi berries, chayote and green tomatoes. Similar to other research projects, many families in this study grew foods that had meaning in terms of their identity as individuals and their personal and community history (Fruge et al 2014;Schupp and Sharp 2012). The agrobiodiversity of the garden contributes to nutrition and food security by increasing the intake of culturally unique vegetables.…”
Section: Increasing Vegetable Consumptionmentioning
confidence: 87%
“…security for an extended network of family and friends should be explored further (Schupp and Sharp 2012). Limitations of our study include the small sample size, the unknown degree of bias due to self-selection and the potential for recall bias in self reporting.…”
Section: Increasing Vegetable Consumptionmentioning
confidence: 99%
“…Nabhan 2002, Renting et al 2003, Selfa and Qazi 2005, Maxey 2006, Steel 2008, Little et al 2009). In the Western social context, literature on FSP explores a range of questions, including the relative importance of economic versus other motivations for participating in FSP (Teitelbaum andBeckley 2006, Schupp andSharp 2012), the extent to which FSP can be considered a form of food localism (McEntee 2010, Schupp andSharp 2012), labour and gender constraints on people's involvement in FSP (McIntyre and Rondeau 2011), the contribution of FSP to local food security and as a source of nutritious food (Shaw 2006, Kortright andWakefield 2011) and the role of spatial planning in facilitating and shaping FSP practices (Adams et al 2013). 3 While there are clearly important differences between promoting organically certified food and food bought directly from a small farmer, ENGO campaigns on these food alternatives rather than FSP could be criticised as being part of an ongoing process of corporatisation or neoliberalisation within ENGOs: unlike FSP, those food alternatives rely on monetised market transactions (e.g.…”
Section: Scholarship On Environmental Activism and Afnsmentioning
confidence: 99%
“…Taylor and Taylor Lovell's (2014, p. 285) "manifesto for the study of home gardens in the Global North" as well as exploratory research into the social base of this form of AFNs (Schupp and Sharp 2012), the barriers to its diffusion (Schupp et al 2015), its environmental sustainability dimensions and its contributions to equity and social justice (Jehlička and Smith 2011, Turner 2011, Smith and Jehlička 2013 have occurred only in the last five years.…”
Section: Introductionmentioning
confidence: 99%
“…In the UK, while demand for allotment sites has waxed and waned, it peaked in 1997 with 296 923 plots established in England and a waiting list of 12 950 people (Gaynor, 2006). The current uptake of backyard food cultivation in developed countries has been partly attributed to popular environmental writers and speciality gardening and cooking shows promoting domestic food production for the masses (Schupp & Sharp, 2011). Australia's re-engagement with community gardening and productive backyard gardening also started in the 1970s.…”
Section: Community and Backyard Food Gardeningmentioning
confidence: 99%